The Effect of Social Influence on Students’ Purchase Decision at Marketplace of Shopee - Al Karimah, Fida Lu'luk; Nurdin, Nurdin; Hestiningtyas, Widya (Journal of Economics Education and Entrepreneurship, 2022)
The digital age which is signed by the use of internet media on business through various channels such as electronic commerce (e-commerce) creates a new thing of consumer behavior particulary on students. The aims of this study were to find out the effect of social influence on students’ purchase decision at marketplace of Shopee. This research is categorized into quantitative research and used a verificative description method. The data were collected using observation and online questionnaire technique. The sampling technique of this research used a purposive sampling with total of the samples were of 91 students who had been purchasing at Shopee. The analysis result showed that there was a positive and significant effect of social influence on purchase decision at marketplace of Shopee is 31,7%. Briefly, the hypothesis proposed in this research was accepted. In conclusion, it can be stated that social influence can effect on students’ purchase decision at marketplace of Shopee.